The Effect of Force Application on the Stability of Mini-Screw in Different Insertion Angles (An in-vitro Study). - Lazha Latif Binyamen; Zana Qadir Omer (Erbil Dental Journal)
Background and Objective: The stability of the mini-screw is an important factor for the success of orthodontic treatment using an absolute anchorage system. This study aims to evaluate the ideal insertion angle of a mini-implant in relation to force direction and to evaluate the maximum amount of force application at a specific angular configuration. Method: In this experimental study 72 mini-screws were used, 36 of them were used for each shear and tensile force tests, eighteen samples were taken for the bone density D2 (nine for 60ₒ angle, and nine for 90ₒ angle), and 18 others were taken for the bone density D3 (nine for 60ₒ angle, and nine for 90ₒ angle). Guiding stents were fabricated for proper insertion angle, torque and speed were controlled by contra -angled handpiece. Shear and tensile force tests are done with the aid of a Universal Testing Machine. Results: Mini-implants inserted at 90̊ angle over D2 density bone had higher stability when performing the tensile force test, while in the shear force test mini-implants placed at 60̊ angle were more stable when inserted on bony blocks with D3 density, however it was noted that the results were statistically not significant when compared with 60̊ insertion on blocks with D2 density. Conclusion: To maintain a stable mini-implant during the orthodontic process, the ideal insertion angle is 90̊ when the force direction is vertical, tensile force, and its more appropriate to place the mini-implant at 60̊ angle when the direction of force is in a horizontal direction, shear force.